مضامين الإصلاح التربوي في الجزائر بين التنظير والتطبيق - بن خيرة, عيسى; حنطابلي, يوسف (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة لمعرفة واقع تطبيق مضامين الاصلاح التربوي في المؤسسات التربوية بالجزائر بين ما هو مقرر وما هو مطبق، ولتحقيق أهداف الدراسة اعتمدنا المنهج الوصفي التحليلي، و على الاستبيان لجمع البيانات ببعض ثانويات الجلفة، وخلصت نتائج الدراسة الى أن واقع الثانويات غير مهيأ لتطبيق مضامين هذه الإصلاحات، وأن هناك تطبيق متباين لها من قبل الأساتذة، ولم تكن لهم مساهمة في صياغة مضامين الإصلاح التربوي المقررة، مما يستدعي إعادة النظر فيها. This study aimed to know the reality of applying the contents of educational reform in educational institutions in Algeria, between what is decided and what is implemented, and to achieve the objectives of the study we adopted the descriptive analytical approach, and the questionnaire to collect data in some secondary schools in Djelfa. and that there is a Different application of them by the professors, and they did not have a contribution to formulating them, which calls for reconsideration.
مقال
Keywords: مضامين الاصلاح التربوي ؛ النظام التربوي؛ التربية; implications of educational reform; The educational system; Education